Management and Leadership Development - Christoper Mabey, Tim Finch-Lees (Sage, 2008)
Chris Mabey and Tim Finch-Lees provide a fresh analysis of the concept and practice of management and leadership development (MLD). Grounded in research, the authors set out the current state of management and leadership development practices, before introducing readers to competing theories of MLD and offering them a more critical perspective. Throughout the book, ideas are illustrated by international case studies and vignettes that evoke the perceptions and interests of the whole range of stakeholders in the management development process.